BNN/TiO2 nanocomposite system–modified dental flow resins and the mechanism of the enhancement of mechanical and antibacterial properties. (24th February 2023) - Kong, Xinzi; Han, Qize; Jiang, Axue; Wang, Yurui; Li, Ruizhi; Wang, Yuting; Xiao, Shengjie; Wei, Rong; Ma, Yu
Abstract : The mechanical and antibacterial properties of dental resins are found to improve by introducing multi-dimensional nanocomposites which provide new insights for the preparation of functional resins and the synergy of nanosystems. Abstract : Robust and antibacterial dental resins are essential for repairing the shape and function of the teeth. However, an ingenious way to achieve a synergistic enhancement of these two properties is still lacking. In this work, guided by molecular dynamics (MD) calculations, a boron nitride nanosheet (BNN)/titanium dioxide (TiO2 ) nanocomposite system was synthesized and used to modify the dental flow resin to enhance its mechanical and antimicrobial properties. The mechanical and antimicrobial enhancement mechanisms were further explored. The modified resin demonstrated outstanding performance improvement with 88.23%, 58.47%, 82.01%, and 55.06% improvement in compressive strength (CS), microhardness (MH), flexural strength (FS), and elastic modulus (EM), respectively. Moreover, the modified resin could effectively inhibit the growth of Streptococcus mutans ( S. mutans ) regardless of aging in water and the inhibition rates were more than 90%. In conclusion, the modified resin is expected to be an ideal restorative material for clinical applications.